Contributing to the Realization of a Truly Just, Independent, and Peaceful Philippines - US, NDF (Kasarinlan: Philippine Journal of Third World Studies; Vol 8 No 4 (1993): The NDF at 20: A Front United?, 2008)
NDF-US Vision Statement.